Connecting urban green and blue spaces with children’ health: a bibliometric analysis in CiteSpace and VOSviewer - Kang, Yutong; Guo, Zhengbing (Frontiers in Psychology, 2025)
IntroductionRapid urbanization has increasingly restricted children’s access to natural environments, raising concerns about potential consequences for their physical, mental, and social well-being. Urban green and blue spaces are known to offer significant health benefits, including physical activity promotion, psychological restoration, and social development.MethodsThis study conducted a comprehensive bibliometric analysis to examine the relationship between urban green/blue spaces and children’s health. A total of 575 relevant publications from 1981 to 2024 were retrieved from the Web of Science database. CiteSpace and VOSviewer were used for keyword co-occurrence analysis, co-citation mapping, and burst detection to visualize research trends and thematic evolution.ResultsThree major research phases were identified: (1) early focus on physical health outcomes, (2) a shift toward urban environmental contexts, and (3) emerging emphasis on sustainability, environmental quality, and walkability. While green spaces have been extensively studied, blue spaces remain underrepresented, especially in terms of their synergistic benefits when combined with green spaces. Key research themes include mental and physical health impacts, social skills development, and the educational functions of nature exposure.DiscussionThis study reveals the interdisciplinary and collaborative nature of current research and emphasizes the importance of ensuring equitable access to high-quality natural environments in urban areas. The findings offer practical implications for urban planners and policymakers and establish a research foundation for promoting sustainable urban development that supports children’s health and well-being.